The Government's Role in the Family Hope Program (PKH) as an Effort to Reduce Poverty in Kamarian Village, Kairatu District, West Seram Regency - Elias, Krisye Heidi; Tuharea, Jumiati; Soumokil, Agustinus (Jurnal Pendidikan Amartha, 2023)
The purpose of this study is to determine the process of implementing the family hope program and the impact of family hope on poor families. The type of research used is descriptive research with a qualitative approach. The data collection technique in this study is an interview, which is used to obtain information by asking directly to informants using interview guidelines in accordance with the problem studied. Documentation researchers obtain data by collecting data sourced from written data, archives and images related to the family hope program (PKH). Kamarian Village is one of the villages that has implemented the PKH program since 2012 until now. From the results of the study, it shows that the process of implementing the family hope program (PKH) is running well, this can be seen from all activities in the implementation of the policy that are carried out well. The positive impact of the implementation of the PKH program is the improvement of health, education, and improvement of social welfare and can help reduce the burden of income expenditure as well as behavior change and independence of PKH families and other poor families.